SHARIA BANKING STRATEGY IN DEALING WITH FINANCIAL TECHNOLOGY A REVIEW OF THE LITERATURE - Erlindawati, Erlindawati; Hendri, Zul; Suhartini, Ade; Eryana, Eryana (Fakultas Agama Islam, Universitas Ibn Khaldun Bogor, 2023)
The purpose of this study is to determine the strategy of Islamic banking to deal with the development of Financial Technology (Fintech). This study uses a literature study technique in search of relevant theories to answer research problems related to the strategy of Islamic banks in dealing with financial technology. The results of this study reveal that a strategy that can be applied by banks to deal with the development of financial technology is the Collaborating Strategy of collaborating with businesses offered by fintech companies so that they can jointly build a platform that facilitates both businesses. Sharia Banking Channeling Strategy with Fintech by promoting a lending-based fund distribution model where the risk is borne by the banking itself, while fintech companies only have limited authority over the contents of the contract. Confotative Strategy by building a new company model with the current startup format. Sharia Banking Digitalization Strategy by utilizing technological advances to improve the quality of banking services. Improving the quality of human resources as actors in sharia banking and innovating sharia banking products.